Mengatasi Permasalahan dalam Penyaluran Bansos Berdasarkan Unsur-Unsur Komunikasinya - Sopian Sopian; R Hiru Muhammad; Asep Rahman Umbara; Mirza Shahreza (Yayasan Literasi Sains Indonesia, 2026)
Social assistance programs often face problems. The purpose of this study is to identify causes of these problems and solutions, primarily related to communication elements that accompany program implementation. This qualitative descriptive research uses a literature review. Data are analyzed to answer the objectives. The results showed that problems in the social assistance program are essentially due to poor data integration and integrity, weak oversight systems, corruption, and political intervention. In the communication element, these problems are included in the environmental element (from bureaucracy, data, and systems that are also problematic). The problems in this element trigger problems in other communication components, which are: the communicators, messages, channels, receivers, and effects. Its each solution: digitalization procedures, real-time data synchronization, transparency, law enforcement; improving integrity, ethics, and data understanding of service communicators in the field; information must be clear, open, persuasive, and educational regarding rights and assistance procedures; integration of digital channels and personal channels; encourage a proactive public and take firm action against laws; strive for a positive impact on social assistance recipients. The research recommends a communication strategy model for social assistance distribution, taking into account each element of communication.